Multi-trait selection indices for improving overall genetic value of Murrah buffaloes - KUMAR, DHIRENDRA; SINGH, HARPAL; KUMAR, D; SINGH, C V (The Indian Journal of Animal Sciences, 2014)
Standard multi-trait selection indices (28) were constructed using records of 1214 Murrah buffaloes under 97 sires for weight at first calving (X1), age at first calving (X2 ), first lactation 300 day milk yield (X3), first lactatior period (X4), first calving interval (X5), first lactation milk yield per month of age at first calving (X6) and first lactation milk yield per day of first calving interval (X7). The correlation between index and aggregate genotypic values (RIH) and expected genetic gains (delta H) ranged from 0.21 to 0.27 and 6.81 to 9.56 units respectively. Based on aggregate genetic gain (t.H) and RIH values. index I1 incorporating all the traits under consideration was most efficient index followed by index 13 which excluded age at first calving and included remaining 6 traits. On the basis of reduction in aggregate genetic gain (delta H) and RIH value due to non-inclusion of different traits in indices, first lactation 300 day milk yield, weight at first calving, first lactation milk yield per month of age at first calving, first calving interval, first lactation period, first lactation milk yield per day of first calving interval and age at tirst calving were important traits in that order. As per the highest delta H and RIH values the following best 2 selection indices could be recommended to improve overall genetic merit of buffaloes. I1= 0.20(X1)+0.12(X2)-0.02(X3)-0.35(X4)+0.05(X5)+ 1.92(X0)+ 11.46 (X7) I3 = 0.20(X1)-0.02(X3)-0.34(X4)+0.05(X5)+ 1.88(X6) + 11.46(X7) Index 3 could be preferred over I1 as it will reduce the cost of statistical analysis. AFC was not found an important trait for inclusion in the index.